Disturbance history is a key driver of tree life span in temperate primary forests. (23rd September 2021) - Pavlin, Jakob; Nagel, Thomas A.; Svitok, Marek; Pettit, Joseph L.; Begović, Krešimir; Mikac, Stjepan; Dikku, Abdulla; Toromani, Elvin; Panayotov, Momchil; Zlatanov, Tzvetan; Haruta, Ovidiu; Dorog, Sorin; et al.
Abstract: Aims: We examined differences in life span among the dominant tree species (spruce, Picea abies ; fir, Abies alba ; beech, Fagus sylvatica ; and maple, Acer pseudoplatanus ) across primary mountain forests of Europe. We asked how disturbance history, lifetime growth patterns, and environmental factors influence life span. Locations: Balkan Mountains, Carpathian Mountains, Dinaric Mountains. Methods: Annual ring widths from 20, 600 cores from primary forests were used to estimate tree life spans, growth trends, and disturbance history metrics. Mixed models were used to examine species‐specific differences in life span (i.e., defined as species‐specific 90th percentiles of age distributions), and how metrics of radial growth, disturbance parameters, and selected environmental factors influence life span. Results: While only a few beech trees surpassed 500 years, individuals of all four species were older than 400 years. There were significant differences in life span among the four species (beech > fir > spruce > maple), indicating life history differentiation in life span. Trees were less likely to reach old age in areas affected by more severe disturbance events, whereas individuals that experienced periods of slow growth and multiple episodes of suppression and release were more likely to reach old age. Aside from a weak but significant negative effect of vegetation season temperature on fir and maple life span, no other environmental factors included in the analysis influenced life span. Conclusions: Our results indicate species‐specific biological differences in life span, which may play a role in facilitating tree species coexistence in mixed temperate forests. Finally, natural disturbance regimes were a key driver of life span, which could have implications for forest dynamics if regimes shift under global change. Abstract : We examined differences in life spans and their drivers among the dominant tree species across primary mountain forests of Europe. Significant differences were found in life spans among the four studied species ( Fagus sylvatica  >  Abies alba  >  Picea abies  >  Acer pseudoplatanus ). Disturbance regimes and not environmental conditions were identified as the main driver of life span variability in primary forests.